Retraction Notice: Application of Internet Fusion Document Recognition in the Realization of Legal Wisdom Guiding Platform with R - Wu, Jing (2022 6th International Conference on Intelligent Computing and Control Systems (ICICCS), 2022)
In the construction of smart legal teaching based on the R platform, in terms of teaching concept, it is necessary to pay attention to the cultivation of morality; in terms of education mode, it is necessary to emphasize individualized cultivation; in terms of teaching methods, it is necessary to implement smart education, realize the sharing of educational resources, and fully Encourage the use of the "technology + education" approach to realize the intelligence of specific educational means. After the integration of document subject information, the evaluation performance has been further improved in some systems. Experiments in the lexical cohesion part also show that the proposed sum is superior in document evaluation, and they give the best fusion evaluation results in most cases.